Kinerja UKM Batik di Jawa Timur dari Perspektif Sumber Daya Perusahaan dan Inovasi Produk - Andrias Dwimahendrawan (Universitas Merdeka Madiun, 2020)
Abstractâ€” This study aims to explain the effect of company resources and product innovation on company performance. This study uses a quantitative approach with a population of 120 batik SMEs and sampling using the Slovin formula with a total of 92 batik SMEs in East Java. Data analysis using linear regression. The results showed that the variable company resources had a significant effect on company performance with a t value of 2.7 and product innovation had a significant effect on company performance with a t value of 2.2. The originality of this study measures the company's performance from the perspective of resources and product innovation in batik SMEs in East Java.Â Keywordsâ€”: Company Resources; Product Innovation; Company performance; Batik.